IDENTIFICATION ISSUES AND PROBLEMS FOR COASTAL DEVELOPMENT IN THE GULF LAMPUNG (AN APPROACH OF SOCIAL ECOLOGICAL SYSTEM) - M. Nur Arkham; Yudi Wahyudin; Achmad Fahrudin; Novit Rikardi; Galih Rakasiwi; Muhammad Reza Pahlevi; Arif Trihandoyo (COJ (Coastal and Ocean Journal), 2018)
Lampung Province has a large potential of coastal and marine resources, but its utilization is not optimal. The aim of the research is to study the potential of coastal and marine resources and identification issues and problems for coastal and marine development program of the Lampung Bay with a social ecological system (SES) approach. The research location is the coastal area of Lampung Bay (Pesawaran District, South Lampung District, and Bandar Lampung City). The data collected by surveys and interviews, while also conducted Focus Group Discussion (FGD). Analysis of the data using the important value index (IVI). The interaction between the components of the resource with resource users, namely commodity of shrimp aquaculture, hatchery of shrimp seeds, seaweed, grouper aquaculture (KJA), capture fisheries, and ecotourism (marine tourism). Interaction between infrastructure components and infrastructure providers, namely long international port commodities, container terminals, jetties, and fish landing base (TPI). The important value index which is included in the category of issues and issues that are very important in carrying out development in the coastal area of Teluk Lampung is the economic field with a value of 2.55 and socio-institutional values of 2.52. Keywords: social ecological system, important value index, ICM and Lampung Bay